The little village of book lovers : a novel [large type] - George, Nina, 1973- (Random House Large Print, 2023)
"In a little town in the south of France in the 1960s, a dazzling encounter with Love itself changes the life of little Marie-Jeanne forever. As a girl, Marie-Jeanne realizes she can see the marks Love has left on the people around her--little glowing lights on the faces and hands that shimmer more brightly when the one meant for them is near. Before long, Marie-Jeanne is playing matchmaker, bringing true loves together in her little town. As she grows up, she helps her father begin a mobile library that travels all throughout the many small mountain towns in the region, and finds herself bringing soulmates together every place they go. In fact, the only person that she can't seem to find a soulmate for is herself. She has no glow of her own, though she waits and waits for it to appear. Everyone must have a soulmate, surely--but will Marie-Jeanne be able to recognize hers when Love finally comes to her?"--